Compression and mechanical connectors for power cables. Test methods and requirements for compression and mechanical connectors for power cables for rated voltages above 1 kV (Um = 1, 2 kV) up to 36 kV (Um = 42 kV) tested on non-insulated conductors Part 1-3, (8th October 2019) - British Standards Institution,
No abstract available